STRATEGI PENINGKATAN KUALITAS LAYANAN SYARIAH TERHADAP NASABAH PADA BANK SYARIAH INDONESIA AREA JAMBI KCP HAYAM WURUK - Neneng Sudharyati; Dessy Anggraini (MARGIN: Journal of Islamic Banking, 2024)
This article explains the strategy for improving the quality of sharia services to customers at Bank Syariah Indonesia Jambi Area KCP Hayam Wuruk. This study is based on the fact that banks as service providers need to implement ways to improve the quality of their services in order to use available resources effectively. Real competitive advantage comes from providing quality services. This is due to the bank's ability to keep its customers happy and focused on their business. The purpose of this research is to determine the strategies and efforts of Bank Syariah Indonesia Jambi Area in improving the quality of sharia services to customers. The research method used in this research is field research with a qualitative approach. The results of this study, Bank Syariah Indonesia Jambi Area is AKHLAK (Trusted, Competent, Harmonious, Loyal, Adaptable, Physical, Human Resources, Business Services, Business realizes the value of collaboration through the ultimate business acceleration concept to increase contributions to and obstacles faced by BSI is to always achieve excellent service by providing excellent service to customers and convenient solutions for the work of its employees, so that the service is optimal and hassle-free.